2011
DOI: 10.1038/modpathol.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Molecular discrimination of cutaneous squamous cell carcinoma from actinic keratosis and normal skin

Abstract: Actinic keratosis is widely believed to be a neoplastic lesion and a precursor to invasive squamous cell carcinoma. However, there has been some debate as to whether actinic keratosis is in fact actually squamous cell carcinoma and should be treated as such. As the clinical management and prognosis of patients is widely held to be different for each of these lesions, our goal was to identify unique gene signatures using DNA microarrays to discriminate among normal skin, actinic keratosis, and squamous cell car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 64 publications
3
48
0
2
Order By: Relevance
“…The ten cases of squamous cell carcinoma that were used for the comparison were previously reported. 8,9 They consisted of well-to-moderately differentiated squamous cell carcinoma arising from skin showing actinic damage with solar elastosis and/or actinic keratosis. The ten cases of keratoacanthoma included sporadic keratoacanthomas and BRAF inhibitor-induced keratoacanthomas.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ten cases of squamous cell carcinoma that were used for the comparison were previously reported. 8,9 They consisted of well-to-moderately differentiated squamous cell carcinoma arising from skin showing actinic damage with solar elastosis and/or actinic keratosis. The ten cases of keratoacanthoma included sporadic keratoacanthomas and BRAF inhibitor-induced keratoacanthomas.…”
Section: Sample Selectionmentioning
confidence: 99%
“…10 Methods of RNA isolation, quality control, target preparation and microarray hybridization, and data analysis are described below and in our previous studies. 8,9 RNA Isolation and Quality Control Total RNA was isolated using the Ambion RecoverAll (Applied Bio systems/Ambion, Austin, TX, USA) kit according to the manufacturer's instructions. Briefly, formalin-fixed and paraffin-embedded samples were deparaffinized by using a series of xylene and ethanol washes and then subjected to a proteinase K digestion at 50 1C for 16 h to release RNA from covalently linked proteins.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Direct evidence of this has subsequently been found by a number of gene expression array analyses in cSCC samples, which have identified increases in the mRNA levels of WNT ligands and their receptors, and in some samples also the down-regulation of endogenous secreted WNT inhibitors such as secreted FZD-related proteins (SFRPs) that antagonise WNT-FZD interactions (Haider, et al 2006;Ra, et al 2011;Watt, et al 2011). For example, Haider and colleagues found that WNT5A and FZD6 were both upregulated in cSCC (Haider, et al 2006), whilst a study by Ra et al identified the WNT signaling network as the most significantly enriched set of molecular pathways in gene expression comparisons between cSCC and normal skin (Ra, et al 2011). Evidence for enhanced β-catenin signaling in cSCC comes from a number of immunohistochemical staining studies on cSCC tumors, looking at β-catenin levels in tumours.…”
Section: Wnt Signaling In Csccmentioning
confidence: 95%
“…One of the earliest studies using comparative genomic hybridization found frequent amplification of chromosomes 7q, 8q, 11q and 17q in cSCC lines, which all contain WNT and/or FZD genes, suggesting that expression of these genes may 7 be increased in cSCC (Popp, et al 2002). Direct evidence of this has subsequently been found by a number of gene expression array analyses in cSCC samples, which have identified increases in the mRNA levels of WNT ligands and their receptors, and in some samples also the down-regulation of endogenous secreted WNT inhibitors such as secreted FZD-related proteins (SFRPs) that antagonise WNT-FZD interactions (Haider, et al 2006;Ra, et al 2011;Watt, et al 2011). For example, Haider and colleagues found that WNT5A and FZD6 were both upregulated in cSCC (Haider, et al 2006), whilst a study by Ra et al identified the WNT signaling network as the most significantly enriched set of molecular pathways in gene expression comparisons between cSCC and normal skin (Ra, et al 2011).…”
Section: Wnt Signaling In Csccmentioning
confidence: 98%
See 1 more Smart Citation